2016
DOI: 10.1039/c6nr07255k
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-mediated clearance of ubiquitinated mutant huntingtin by graphene oxide

Abstract: Many of the neurodegenerative disorders such as Huntington's disease (HD) are caused by the accumulation of intracytoplasmic aggregate-prone proteins. These toxic protein aggregates are mainly degraded by autophagy, thus elevating the autophagy level to enhance the degradation of these proteins representing an emerging viable approach for the treatment of neurodegenerative diseases. In this report we showed that graphene oxide (GO), an engineered nanomaterial with enormous potential in biomedical applications,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…In this study, the expression of PI3K/Akt/mTOR, a main upstream signaling pathway of autophagy, was further studied by Western blot analysis, and the results suggested that GO-induced autophagy was activated by suppressing the PI3K/Akt/mTOR signaling pathway. Previous studies have shown that GO-activated autophagy does not involve the mTOR pathway but depends on activation of the PtdIns3K and MEK/ERK1/2 signaling pathways [61]. A recent study also suggested that downregulation of PI3K/Akt/mTOR signaling pathways leads to GOinduced autophagy [31].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the expression of PI3K/Akt/mTOR, a main upstream signaling pathway of autophagy, was further studied by Western blot analysis, and the results suggested that GO-induced autophagy was activated by suppressing the PI3K/Akt/mTOR signaling pathway. Previous studies have shown that GO-activated autophagy does not involve the mTOR pathway but depends on activation of the PtdIns3K and MEK/ERK1/2 signaling pathways [61]. A recent study also suggested that downregulation of PI3K/Akt/mTOR signaling pathways leads to GOinduced autophagy [31].…”
Section: Discussionmentioning
confidence: 99%
“…These data demonstrate the important role of autophagy in midazolam-induced mHtt protein accumulation. UPS, another important pathway for proteolysis in eukaryotes, could be inhibited by MG132 [22]. However, there was no significant change in the percentage of GFP-Htt (Q74) puncta or in GFP-Htt (Q74) protein levels between midazolam-and MG132 plus midazolamtreated cells (Fig.…”
Section: Role Of Autophagy In Midazolam-induced Gfp-htt (Q74) Accumulmentioning
confidence: 88%
“…In these cells, GFP-Htt (Q74) protein was observed as bright punctate dots [22], indicating the formation of aggregates. As shown in Fig.…”
Section: Midazolam Induced Gfp-htt (Q74) Accumulationmentioning
confidence: 99%
“…In Eu III (OH) 3 nanorod‐induced autophagy, the autophagy induction is regulated not only by MEK/ERK1/2 signaling pathway but also by AKT–mTOR and AMPK‐independent pathway, and the activation of autophagy caused by Eu III (OH) 3 nanorods is dose‐ and time dependent . In another research, GO‐induced autophagy was shown to be mediated by PI3K and was dependent on MEK/ERK1/2 but not on mTOR signaling pathway in PC12 and Hela cells . To further enhance or reduce the autophagy degree and more exactly depict the regulatory mechanisms of NM‐phagy, some interference including autophagy drug regulator (such as 3‐MA and trehalose) or gene silencing are usually used in NM‐phagy…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…For example, compared to larger one, the small silica nanoparticles (SNPs) enhance the endocytosis properties, which probably due to the fact that small‐sized NMs can be rapidly and favorably internalized into cells than large ones . The fact may also reason the observation that small graphene oxide (GO)‐induced autophagy‐mediated clearance of huntingtin is more effective than large one, while, in some cases, the larger NMs show higher efficient endocytosis than small one, such as the AuNPs . The effect of shape on endocytosis has been described by many researches.…”
Section: Endocytosis Pathways Of Nmsmentioning
confidence: 99%